In Situ Confining Pt Clusters in Ultrathin MnO2 Nanosheets for Highly Efficient Hydrogen Evolution Reaction. Issue 9 (7th July 2021) - Wei, Jin-Xin; Cao, Mei-Zhi; Xiao, Kang; Guo, Xing-Peng; Ye, Si-Yu; Liu, Zhao-Qing
Abstract : Rational synthesis of highly dispersed electrocatalyst with excellent electrocatalytic performance is critical for energy and environment applications. However, metal cluster with high surface free energy remains a challenge for the synthesis of stable and highly active catalysts. Herein, a highly dispersed platinum cluster anchored on the Mn vacancy of MnO2 nanosheets (PtAC ‐MnO2 ) via in situ electrochemical methods is reported. The strongly binding energy between Pt clusters and supports can effectively suppress the migration of active Pt atoms and optimize their electronic structure for excellent electrocatalytic properties. Impressively, the PtAC ‐MnO2 demonstrates a considerably low overpotential ( η 100 ) of 47 mV at 100 mA cm −2 and can be catalyzed continuously at 10 mA cm −2 for 80 h, showing better catalytic stability than the state‐of‐the‐art commercial Pt/C catalysts. A cationic vacancy defect strategy for the design and preparation of metal cluster catalysts is provided. Abstract : Herein, highly dispersed Pt clusters are anchored in the Mn vacancies of MnO2 nanosheets by a simple in situ electrochemical method. The unique Pt–O coordination with ligand unsaturated O atoms, optimizes the electronic structure and density of states of the catalyst, effectively limits Pt atom migration, and thus improves hydrogen evolution activity and stability.